The frequency of the ACTN3 polymorphism in Brazil: a systematic review and meta-analysis - Valmir Oliveira Silvino; Cirley Pinheiro Ferreira; Helen Matias Apaza; Valtemir Silvino de Souza-Junior; Sérgio Luís Galan Ribeiro; Sandro Soares Almeida; Marcos Antonio Pereira dos Santos (BMC Medical Genomics)
Abstract Background The ACTN3 gene encodes the protein alpha-actinin-3, which is crucial for fast-twitch muscle fibers, contributing to rapid and forceful contractions. The distribution of these genotypes and their impact on sports performance in Brazilian populations are not well-documented. This study aimed to determine the allelic and genotypic frequency of the ACTN3 R/X polymorphism in Brazil and its association with sports performance. Methods A systematic review was conducted, including studies sourced from PubMed, Scielo, LILACS, LIPECS, Coleciona SUS, CUMED, BINACIS, IBECS, and MEDLINE databases, resulting in 42 studies included. The quality of these studies was assessed using the Strengthening the Reporting of Genetic Association (STREGA) guidelines. Results Among all the 8,746 participants, 35.2% had the RR genotype, 46.2% had the RX genotype, and 18.6% had the XX genotype. Regarding allelic frequency, 58.3% were R allele carriers, while 41.7% were X allele carriers. Meta-analysis showed that there was no consistent association between the ACTN3 genotypes and sports performance, although some data suggested potential benefits in athletic performance. Conclusion This study revealed that the RX genotype of the ACTN3 R577X polymorphism is the most prevalent in Brazil, followed by the RR and XX genotypes. While the R allele was more frequent, the meta-analysis did not confirm a consistent association between ACTN3 genotypes and sports performance, suggesting that other genetic and environmental factors contribute to athletic success.